The Role of Individual-Level Factors in Rural Mortality Disparities - Erika Rees-Punia, PhD, MPH; Emily Deubler, MSPH; Alpa V. Patel, PhD; W. Ryan Diver, MSPH; James Hodge, JD, MPH; Farhad Islami, MD, PhD; Min Jee Lee, PhD, MPH; Marjorie L. McCullough, ScD, RD; Lauren R. Teras, PhD (AJPM Focus, 2022)
Introduction: The role of individual risk factors in the rural‒urban mortality disparity is poorly understood. The purpose of this study was to explore the role of individual-level demographics and health behaviors on the association between rural residence and the risk of mortality. Methods: Cancer Prevention Study-II participants provided updated addresses throughout the study period. Rural‒Urban Commuting Area codes were assigned to participants’ geocoded addresses as a time-varying exposure. Cox proportional hazards regression was used to estimate hazard ratios and 95% CIs for mortality associated with Rural‒Urban Commuting Area groups. Results: After adjustment for age and sex, residents of rural areas/small towns had a small but statistically significant elevated risk of all-cause mortality compared with metropolitan residents (hazard ratio=1.04; 95% CI=1.01, 1.06). Adjustment for additional covariates attenuated the association entirely (hazard ratio=0.99; 95% CI=0.97, 1.01). Individually, adjustment for education (hazard ratio=0.99; 95% CI=0.97, 1.01), alcohol use (hazard ratio=1.01; 95% CI=0.99, 1.04), and moderate-to-vigorous intensity aerobic physical activity (hazard ratio=1.00; 95% CI=0.97, 1.02) eliminated the elevated risk. Conclusions: The elevated risk of death for rural compared with that for metropolitan residents appeared to be largely explained by individual-level demographics and health behaviors. If replicated in other subpopulations, these results suggest that modifiable factors may play an important role in reducing the rural mortality disparity.